Healthy PNPLA3 Risk Allele Carriers Present with Unexpected Body Fat Composition. A Study of One ousand Subjects - Kempinska-Podhorodecka, Agnieszka; Krawczyk, Marcin; Klak, Marta; Blatkiewicz, Malgorzata; Lammert, Frank; Milkiewicz, Piotr; Milkiewicz, Malgorzata (Journal of gastrointestinal and liver diseases : JGLD, 2014)
Introduction: The common PNPLA3 (adiponutrin) variant p.I148M represents a major genetic driver of progression in non-alcoholic fatty liver disease (NAFLD). NAFLD is commonly associated with traits of the metabolic syndrome, therefore it is mostly suspected in obese individuals. Here, we investigate the association between the PNPLA3 variant and anthropometric traits in a cohort of healthy individuals.Patients and methods: We recruited 1,000 (500 females; age 18 - 66 years) healthy blood donors. The PNPLA3 variant was genotyped using TaqMan assays. All individuals were phenotyped with respect to anthropometric characteristics. We also determined the percentage of total fat (F%) and active tissue (TA%) of body weight.Results: Healthy carriers of the PNPLA3 [IM] and [MM] genotypes, although not differing in height from individuals with the genotype [II], displayed significantly lower body weight and lower BMI (both P = 0.005), higher TA% (P = 0.03) but lower F% (P = 0.03) and smaller waist, chest and shin circumferences (all P < 0.05). Separate analysis for males and females demonstrated an association between the [IM] and [MM] genotypes and higher TA% but lower F% (P = 0.04) in females. In males, BMI and total weight were significantly (P = 0.04) lower among carriers of the [M] allele.Discussion: Healthy individuals carrying the prosteatotic PNPLA3 allele p.I48M may be leaner as compared to the carriers of the common allele. Hence in clinical practice they might be overlooked since they do not necessarily present with the anthropometric characteristics commonly associated with severe hepatic steatosis.Abbreviations: ATX - autotaxin; BMI - body mass index; F% - total fat of body weight in %; Fkg - total fat of body weight in kilograms; GWAS - genome-wide association study; LPA - lysophosphatidic acid; NAFLD, non-alcoholic fatty liver disease; NASH - non-alcoholic steatohepatitis; PA - phosphatidic acid; PNPLA3-patatin-like phospholipase domain containing 3 (adiponutrin); TA% - active tissue of body weight in %; TAkg - active tissue of body weight in kilograms; WHR - waist-to-hip ratio.